2009
DOI: 10.1097/mjt.0b013e3181727b42
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism in Patients With Atrial Fibrillation With and Without Left Atrial Thrombus Documented by Transesophageal Echocardiography

Abstract: The incidence of cerebrovascular events (CVEs) was investigated in 95 consecutive patients with atrial fibrillation (AF) with left atrial thrombus (LAT) diagnosed by transesophageal echocardiography (TEE) and in 131 age- and sex-matched AF patients without LAT. Compared with patients without LAT, patients with LAT had a larger left atrial diameter (49 versus 44 mm, P < 0.0001), a lower left ventricular ejection fraction (40% versus 50%, P < 0.0001), a higher prevalence of spontaneous echocardiographic contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The optimal therapeutic range for anticoagulation with warfarin in the prevention of thromboembolic events with non-valvular AF patients extends over INR values of 2.0 to 3.0 [6,7]. It has been reported that major bleeding is observed only at INR values above 2.5 on anticoagulation with warfarin [1].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal therapeutic range for anticoagulation with warfarin in the prevention of thromboembolic events with non-valvular AF patients extends over INR values of 2.0 to 3.0 [6,7]. It has been reported that major bleeding is observed only at INR values above 2.5 on anticoagulation with warfarin [1].…”
Section: Discussionmentioning
confidence: 99%
“…The flowchart of the systematic review is depicted in Figure . Of the 8,468 articles screened, 17 articles were selected for the final analyses . The initial and follow‐up data of the articles included in the final analyses are listed in Table and in Table , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles from Creighton University had overlapping populations, but both were retained given different suitability for VKA and warfarin analyses . The study by Nair et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that LAA size is an important factor that determines LAA function. Although transesophageal echocardiography allows the LAA structure to be assessed with high accuracy, some technical problems remain [3,4]. On the other hand, LAA filling detected by 64-slice multidetector computed tomography (64-MDCT) has been reported as a useful modality for imaging the LAA structure [5,6].…”
Section: Introductionmentioning
confidence: 99%